Brief Report: PrEP Use During Periods of HIV Risk Among East African Women in Serodiscordant Relationships. (1st January 2018) - Pyra, Maria; Haberer, Jessica E.; Heffron, Renee; Kidoguchi, Lara; Brown, Elizabeth R.; Bukusi, Elizabeth A.; Asiimwe, Stephen; Celum, Connie; Katabira, Elly; Mugo, Nelly R.; Baeten, Jared M.
Abstract : Background: Pre-exposure prophylaxis (PrEP) is efficacious for African women at risk for HIV, but data on adherence outside clinical trials are sparse. We describe the persistence and execution of PrEP use among women participating in a large open-label PrEP demonstration project, particularly during periods of HIV risk. Setting and Methods: Three hundred ten HIV-uninfected women in HIV serodiscordant couples in Kenya and Uganda were offered and accepted PrEP. Electronic monitoring caps were used to measure daily PrEP adherence. Time on PrEP while at risk for HIV (when the HIV-infected partner was on antiretroviral therapy <6 months) and weekly adherence while on PrEP were calculated and compared among older and younger (<25 years old) women. Results: As defined above, women were at risk for HIV for an average of 361 days; 54% took PrEP during their entire risk period and 24% stopped but restarted PrEP during their risk period. While on PrEP, women took ≥6 doses/wk for 78% of weeks [67% of weeks for women aged <25 years, 80% of weeks for women aged ≥25 years ( P < 0.001)], and ≥4 doses for 88% of weeks [80% for those <25, 90% for those ≥25, ( P < 0.001)]. Compared with historical, risk-matched controls, HIV incidence was reduced 93% (95% confidence interval: 77% to 98%) for all women and 91% (95% confidence interval: 29% to 99%) among women aged <25 years. Conclusion: Women, including young women, in HIV-serodiscordant couples took PrEP successfully over sustained periods of risk. Although young women had lower adherence than older women, they achieved strong protection, which suggests that women can align PrEP use to periods of risk and imperfect adherence can still provide substantial benefit.